Effect of activator nature on the impact behaviour of Alkali-Activated slag mortar. (10th October 2020) - Abubakr, A.E.; Soliman, A.M.; Diab, S.H.
Highlights: The static and dynamic performance of AAS is not similar to OPC systems. AAS shows better behavior under impact loads compared to that of the OPC systems. AAS dynamic response is significantly affected by the activator dosage and modulus. Deformations of AAS under impact loads are affected by activator nature. Abstract: Cement is the main binding material for many military and civilian applications. The response of cement-based materials to kinetic energy, transferred by impact loads, always had attracted researchers working in the protective structures field. As an immerging binding material, alkali-activated material responses to different types of loads, especially dynamic loads, have to be studied. In this study, the effects of activator nature (i.e. silicate modulus (Ms) and sodium oxide dosage (Na2 O%)) on the impact performance of alkali-activated slag (AAS) was investigated. Initially, fresh and hardened properties were evaluated for mixtures with various Ms and Na2 O% values to ensure adequality. The impact absorption assessment was performed using a drop weight test. Results show that AAS exhibited up to 70% and 40% better compressive and tensile strength compared to that of the OPC, respectively. For impact energy absorption, AAS mixtures were obviously better than that of the conventional cement-based materials. The relationship between the static and dynamic performance of AAS is not similar to that in cement-based materials. Deformations and energy absorptions of AAS under impact loads are significantly affected by activator nature. Increasing the Modulus up to 1.5 resulted in about 75% enhancement in the impact energy absorption comparing to that of Ms = 1.